Addressing Sharia issues in cryptocurrency: Analyzing the case of Bitcoin and Blockchain Technology - Sahara Putri Dahlan (Journal of Islamic Economic Insights, 2025)
The emergence of cryptocurrency and blockchain technology has spurred significant advancements in the financial sector, raising questions regarding their compatibility with Sharia law. This study examines the convergence of cryptocurrencies, blockchain technology, and Sharia law, with an emphasis on assessing the compatibility of digital currencies with the principles of Islamic banking. The primary objective is to assess the feasibility of aligning cryptocurrencies, specifically Bitcoin, with Sharia law, and the ethical and operational criteria of Islamic finance. This study analyses the current body of literature and case studies on blockchain technology and its implementation in the Islamic financial system. This study highlights the primary difficulties associated with riba (interest), gharar (uncertainty), and maysir (gambling) in cryptocurrency, which may contradict Sharia rules. The study suggests possible remedies, such as employing different validation methods to reduce concerns related to riba and maysir and linking digital currency to tangible assets to tackle volatility. The main conclusions indicate that standard cryptocurrencies encounter difficulties in conforming to the Sharia norms. However, it is possible to create Sharia-compliant digital currencies (SCDCs) by emphasizing ethical and functional factors. Sovereign Central Digital Currencies (SCDCs) have the potential to serve as reliable and morally sound substitutes for traditional government-issued currencies in countries with Muslim populations and beyond. The article continues by highlighting the necessity for additional investigation into the development of SCDCs, examination of asset-backed currencies, and incorporation of blockchain technology in Islamic banking. These advancements have the capacity to transform Islamic finance and make significant contributions to a global economy that is more ethical, transparent, and sustainable